Targeted delivery and controlled release of polymeric nanomedicines for tumor therapy - Na Shen; Weidong Zhao; Hongyu Chu; Haiyang Yu; Hai Sun; Zhaohui Tang; Xuesi Chen (Fundamental Research)
Drug therapy, including chemotherapy and immunotherapy, remains a cornerstone of cancer treatment; however, significant toxic side effects are often unavoidable, inhibiting tumor growth while causing damage to multiple organ systems. Polymeric nanomedicines have shown substantial promise in addressing the limitations of small-molecule drugs, such as poor solubility, rapid clearance, low tumor retention, and adverse effects, thereby enhancing the therapeutic index. Despite these advances, clinical outcomes indicate that the overall survival rates of cancer patients post-treatment are often not significantly higher than those achieved with standard small-molecule drugs. This is largely due to the inadequate tumor targeting and limited tumor penetration of polymeric drugs despite their drug release and targeting capabilities. While actively tumor-targeted and selectively activated drug strategies can potentially improve drug targeting, traditional approaches have yielded unsatisfactory results due to insufficient differences in targets, such as markers and stimuli, between tumor and normal tissues. Recent innovations focus on utilizing drug or external stimuli, such as light, radiation, and ultrasound, to amplify tumor-associated markers or stimuli, enabling more precise tumor targeting and selective drug activation. Based on these innovations, actively targeted or selectively activated polymeric nanomedicines can further enhance drug accumulation within tumors and improve therapeutic outcomes. Moreover, the integration of actively tumor-targeting and tumor-selectively activated strategies represents a significant advancement, which achieves simultaneously enhanced drug accumulation and selective activation within the tumors. This review highlights the significant potential, challenges, and advanced strategies of polymeric nanomedicines in targeted tumor therapy, emphasizing the need for ongoing research to optimize their effectiveness and ultimately improve patient outcomes, paving the way for more effective and less toxic cancer treatment options.